A Sustainable Approach to Flexible Electronics with Zinc‐Tin Oxide Thin‐Film Transistors. (17th May 2018) - Fernandes, Cristina; Santa, Ana; Santos, Ângelo; Bahubalindruni, Pydi; Deuermeier, Jonas; Martins, Rodrigo; Fortunato, Elvira; Barquinha, Pedro
Abstract: Zinc‐tin oxide (ZTO) is widely invoked as a promising indium and gallium‐free alternative for amorphous oxide semiconductor based thin‐film transistors (TFTs). The main bottleneck of this semiconductor material compared to mainstream indium‐gallium‐zinc oxide (IGZO) is centered in the larger processing temperatures required to achieve acceptable performance (>300 °C), not compatible with low‐cost flexible substrates. This work reports for the first time flexible amorphous‐ZTO TFTs processed at a maximum temperature of 180 °C. Different aspects are explored to obtain performance levels comparable to IGZO devices at these low processing temperatures, such as hydrogen incorporation during ZTO sputtering and integration with a high‐κ multilayer/multicomponent dielectric. Close‐to‐zero turn‐on voltage, field‐effect mobility ≈5 cm 2 V −1 s −1, and subthreshold slope of 0.26 V dec −1 are obtained. Stability under negative‐bias‐illumination stress is dramatically improved with hydrogen incorporation in ZTO and device performance is insensitive to bending under a radius of curvature of 15 mm. Inverters using the ZTO TFTs enable rail‐to‐rail operation with supply voltage V DD as low as 5 V, while a differential amplifier with positive feedback loop provides a gain of 17 dB and unity gain frequency of 40 kHz, limited by the large gate‐to‐source and gate‐to‐drain overlaps used herein. Abstract : Flexible zinc‐tin oxide (ZTO) thin‐film transistors (TFTs) processed at only 180 ºC are reported for the first time. Hydrogen incorporation during ZTO sputtering and integration with a high‐κ multilayer dielectric enable ZTO TFTs to present similar performance to indium‐gallium‐zinc oxide TFTs, without using critical elements (In and Ga). Inverters with rail‐to‐rail operation and a differential amplifier with positive feedback loop are demonstrated.